2018
DOI: 10.1016/j.jaerosci.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Survival of aerosolized coronavirus in the ambient air

Abstract: A B S T R A C TAn inactivation of airborne pathogenic Middle East Respiratory Syndrome (MERS-CoV) virus was investigated under controlled laboratory conditions. Two sets of climatic conditions were used in the experiments; (1) representing common office environment (25°C and 79% RH) and (2) climatic conditions of the Middle Eastern region where the virus was originated from (38°C and 24% RH). At the lower temperature, the virus demonstrated high robustness and strong capability to survive with about 63.5% of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 34 publications
4
159
0
7
Order By: Relevance
“…Inactivation studies suggested that survival on surfaces, and in the air, may be further enhanced at relative humidities of less than 50% [40]. These results are consistent with other airborne viruses-including SARS-CoV-1 [21,41], influenza H1N1 [42,43], and MERS-CoV [44][45][46], which also show evidence of airborne transmission. Viability of SARS-CoV-2 in aerosol collected from realworld air samples, however, has not yet been fully explored.…”
Section: Disease Transmission By Sars-cov-2 Aerosolssupporting
confidence: 73%
“…Inactivation studies suggested that survival on surfaces, and in the air, may be further enhanced at relative humidities of less than 50% [40]. These results are consistent with other airborne viruses-including SARS-CoV-1 [21,41], influenza H1N1 [42,43], and MERS-CoV [44][45][46], which also show evidence of airborne transmission. Viability of SARS-CoV-2 in aerosol collected from realworld air samples, however, has not yet been fully explored.…”
Section: Disease Transmission By Sars-cov-2 Aerosolssupporting
confidence: 73%
“…Until now, no evidence has shown that SARS-CoV-2 can survive outside the body for long. However, Middle East respiratory syndrome coronavirus demonstrates high robustness and a strong capability to survive outside the body and can remain infectious for up to 60 minutes after aerosolization (4). Hence, the rapid spread of SARS-CoV-2 in our study could have resulted from spread via fomites (e.g., elevator buttons or restroom taps) or virus aerosolization in a confined public space (e.g., restrooms or elevators).…”
mentioning
confidence: 89%
“…As an RNA virus, MERS-CoV survives surprisingly well on surfaces and in the air, especially at low temperature and low humidity [62]. Sixty minutes after aerosolization, the virus remains infectious at 63.5% at 25 C and 79% humidity, compared with only 4.7% at conditions 38 C and 24% humidity [63]. MERS-CoV was detected by RT-PCR and viral culture up to 18e27 days after symptom onset from most of the touchable environments in patients' rooms [64].…”
Section: Discussionmentioning
confidence: 99%